Short term hydro–wind–thermal scheduling based on particle swarm optimization technique. (October 2016) - Banerjee, Sumit; Dasgupta, Koustav; Chanda, Chandan Kumar
Highlights: A new approach to solve short term hydro–wind–thermal (HWT) scheduling problem. Effect of valve point loading in the fuel cost function of the thermal plants is examined. PSO is applied to find the optimal hourly schedule of generation in a HWT power system. Said method is excellent in terms of convergence characteristic and minimum cost. Abstract: Hydro–wind–thermal scheduling is one of the most important optimization problems in power system. An aim of the short term hydrothermal scheduling of power systems is to determine the optimal hydro, wind and thermal generations in order to meet the load demands over a scheduled horizon of time while satisfying the various constraints on the hydraulic, wind and thermal power system network. In this paper we present optimal hourly schedule of power generation in a hydro–wind–thermal power system applying PSO technique. The simulation results inform that the proposed PSO approach appears to be the powerful to minimize fuel cost and it has better solution quality and good convergence characteristics than other techniques.